Honey : a novel - Thompson, Imani (Random House, 2026)
"A wickedly funny, adrenaline-rush of a novel about a graduate student who murders bad men and justifies it in the name of feminism, by a bold new voice in fiction Yrsa is in a funk. She's bored of her PhD program, bored of her research on Afropessimism, bored of the entitled undergrads she has to cater to. But most of all, she's bored of the men in her life-especially the bad ones. When her best friend, Nina, confesses to having an affair with her professor, and that he's stolen her research, Yrsa is mad. On the quad, Yrsa bumps into the professor and witnesses his death: an unfortunate incident involving his San Pelligrino and a bee allergy. What she sees that afternoon awakens something in her: a taste for murder. Emboldened, Yrsa decides to chase that high, and soon, no sexist, misbehaving man within commuting distance is safe. With each murder, Yrsa feels a greater sense of meaning and purpose-finally, her doctoral research feels useful. But how long can killing in the name of feminist and racial solidarity justify her actions? Will her rampage ever assuage her feelings of rage and revenge? And how long until her actions-and buried family secrets-come back to haunt her?"-- Provided by publisher.